Terra entre rios: figurativizações do Tocantins na poesia de Walace Rodrigues. - Veloso, Iane Barros dos Santos (Universidade Federal do Tocantins, 2022)
This study analyzes images of Tocantins that emerge from the poetic production of the Rio de Janeiro resident writer, Walace Rodrigues. With a recent emancipatory history, one can observe in Tocantins a timid Tocantinian literary expression. The authors who live in the region are poorly read even in the state, the publishers in which they publish have no major projection in the national market, but it is possible to recognize an intense regional production that contributes to shaping a cultural process. In this scenario, Rodrigues' work brings us to a sensitive and poetic understanding of the geographical and historical context of the State of Tocantins, as it privileges the landscape, the subjects and the culture of the place as its theme, building an imaginary about the Tocantins people. and its peculiarities. Poems that thematize the region present in three works, Experiments of Being and Being (2018b), Earth between Rivers (2014) and Interiors (2017), are analyzed here. The qualitative research discusses the challenges faced by the authors in the State, especially considering the still precarious dissemination of local production. It also thematizes the urgency of research that systematizes the characteristics of this emerging production, providing data on Rodrigues' poetry translated into six books / ebooks, published between 2007 and 2018. As theoretical support for analysis, the theoretical foundations of semiotics are mobilized. discursive, understood as theory of meaning and whose works favor the literary text. From the perspective of semiotics, the poems were analyzed from the thematization and figurativization processes, considering the way the texts produce images of the place, from different ways of meaning realization.